Application of sericin‐based edible coating material for postharvest shelf‐life extension and preservation of tomatoes - Korumilli Tarangini; Palepu Kavi; Korukonda Jagajjanani Rao (eFood, 2022)
Abstract This paper studied the effects of sericin‐based edible coating material on the quality and shelf‐life of tomatoes over 40 days of storage at 25°C and relative humidity of 70%. The key constituents of the coating material are sericin (1.5%), chitosan (1.0%), Aloe vera (1.0%), and glycerol (1.5%) in an aqueous solution and applied onto tomatoes in a simple dip‐coating technique. Weight loss, firmness titratable acidity (TA), total soluble solids (TSS), pH, and lycopene content were investigated and scanning electron microscopy was used to observe the semipermeable nature and the thickness of the coating layer. The results stated that the developed coating material reduced weight and firmness losses in tomatoes. With increased storage time, fruit TA content was increased and the values of pH, TSS, lycopene content, total phenolic content, and total antioxidant concentration stood low in comparison with uncoated tomatoes. With no evidence of wrinkles (up to 21 days), visible cracks, or deterioration on coated fruits during the study period, the application of sericin‐based coating might be useful commercially for maintaining the postharvest quality control of tomatoes and even other fruits as well.